Augmenting the Activity of Macrolide Adjuvants against Acinetobacter baumannii - Hubble, Veronica B. (ACS Med Chem Lett, 2020)
[Image: see text] Approximately 1.7 million Americans develop hospital associated infections each year, resulting in more than 98,000 deaths. One of the main contributors to such infections is the Gram-negative pathogen Acinetobacter baumannii. Recently, it was reported that aryl 2-aminoimidazole (2-AI) compounds potentiate macrolide antibiotics against a highly virulent strain of A. baumannii, AB5075. The two lead compounds in that report increased clarithromycin (CLR) potency against AB5075 by 16-fold, lowering the minimum inhibitory concentration (MIC) from 32 to 2 μg/mL at a concentration of 10 μM. Herein, we report a structure–activity relationship study of a panel of derivatives structurally inspired by the previously reported aryl 2-AI leads. Substitutions around the core phenyl ring yielded a lead that potentiates clarithromycin by 64- and 32-fold against AB5075 at 10 and 7.5 μM, exceeding the dose response of the original lead. Additional probing of the amide linker led to the discovery of two urea containing adjuvants that suppressed clarithromycin resistance in AB5075 by 64- and 128-fold at 7.5 μM. Finally, the originally reported adjuvant was tested for its ability to suppress the evolution of resistance to clarithromycin over the course of nine consecutive days. At 30 μM, the parent compound reduced the CLR MIC from 512 to 2 μg/mL, demonstrating that the original lead remained active against a more CLR resistant strain of AB5075.